Front cover: Highly Dispersible and Bioavailable Curcumin but not Native Curcumin Induces Brown‐Like Adipocyte Formation in Mice. Issue 5 (6th March 2018) - Nishikawa, Sho; Kamiya, Misa; Aoyama, Hiroki; Nomura, Mami; Hyodo, Takuma; Ozeki, Aoi; Lee, Hyunjin; Takahashi, Tsukasa; Imaizumi, Atsushi; Tsuda, Takanori
Abstract : Mol. Nutr. Food Res. 2018, 62, 1700731 DOI:10.1002/mnfr.201700731 Highly dispersible and bioavailable curcumin, but not the same dose of native curcumin, induces the formation of brown‐like adipocytes in mouse inguinal white adipose tissue (WAT). This results from the production of local norepinephrine by the accumulation of localized alternatively activated macrophages in inguinal WAT. Further details can be found in article number 1700731 by Takanori Tsuda and co‐workers.